Design of an automatic common water hyacinth flattening machine with an off-grid solar energy system - Adeguna Ridlo Pramurti; Mochammad Muqorrobin; Pangestuningtyas Diah Larasati; Syahid Syahid; Friska Ayu Fitrianti Sugiono (Jurnal Polimesin, 2025)
Transforming common water hyacinths into handicrafts is a viable business opportunity in several regions across Indonesia. One of the crucial processing stages in producing these handicrafts is flattening, which reduces the plant material to approximately 0.2 mm in thickness to ensure optimal weaving quality. The objective of this research is to design an automatic water hyacinth harvesting machine that uses an off-grid solar power plant as its primary energy source. The automation system on this machine uses a Programmable Logic Controller (PLC) as the control system and Supervisory Control and Data Acquisition (SCADA) as the interface and monitoring system. The designed water hyacinth flattening machine increases production capacity to 834 grams in 15 minutes. The size of flattened water hyacinths was 0.2 mm, following the flattening roller setting. The machine's average power consumption is 249 W, which the solar power plant system can supply for approximately 1.5 hours.